ANALISIS PERBANDINGAN TERJEMAHAN UNGKAPAN YANG MENGANDUNG SIKAP SEKSIS ANTARA TOKOH LAKI-LAKI DAN PEREMPUAN DALAM NOVEL RONGGENG DUKUH PARUK - Maria Dita Manggarrani; M.R. Nababan; Riyadi Santosa (Masyarakat Linguistik Indonesia, 2019)
Abstract This research aims to identify the translation techniques which are used to translate utterances containing sexist attitudes on men and women characters in Ronggeng Dukuh Paruk Novel. The researcher also aims to find the translation shift that occured as a result of the translation techniques usage. To analyze the data, the researcher used some analysis steps: taxonomy analysis, componential analysis, and the cultural value analysis. The result shows that there are 14 techniques found. The translator tends to use established equivalent for both men and women characters. Discursive creation and transposition produced translation shift. This shift occured once on the utterances toward men and women. Keywords: Translation; translation techniques; translation shift, sexist attitudes; sexism